(untitled) (CIPEEX, 2022)
Active transportation or active mobility is understood as any form of non-motorized movement that requires some physical effort. International organizations have been encouraging active transportation on the home-to-school route as a way to incorporate physical activity into the daily lives of young people. Among the various forms of active transportation, the most common active commutes are those made on foot or by bicycle. The research measuring the real impact and benefits on the health of people who adopt this mode of transportation, especially in the school context, is still incipient and inconclusive. The present study aims to evaluate the impacts of active transportation on the increase of physical activity, health, and well-being of schoolchildren. This is a prospective cohort analytical observational study. The groups will be classified as users and non-users of active transportation on the home-to-school route. Adolescents aged between 10 and 17 years who are regularly enrolled in state public schools under the Regional Coordination of Education of Goianésia, covering 8 municipalities, will participate in the study. Approximately 375 participants are estimated. The variables, physical activity and active commuting, will be assessed at two distinct times (beginning and end of the academic semester).